2020
DOI: 10.1055/s-0041-1723078
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Prognosis of Epidermal Growth Factor Receptor Variant III Mutations in Glioblastoma Multiforme among Indian Patients: A Single-Institution Study

Abstract: Background Glioblastoma multiforme (GBM) is a disease with poor outcome. Alterations or mutations in epidermal growth factor receptors (EGFRs) are found in GBM and may be targeted to improve outcomes. Aims We analyzed the frequency of EGFR variant III (vIII) mutations in patients with GBM and their outcomes after standard treatment. Materials and Methods This is a retrospective study conducted in a single tertiary cancer center in south India. Forty patients with GBM who had their entire tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
4
1
2
Order By: Relevance
“…In our study, the male-to-female ratio was estimated to be 2:1 and 1.4:1 in EGFR-vIII positive cases aged ≤40 years and >40 years, respectively, while in the study of Jose et al, it was found to be 1:1 in ≤40 years and male predominance in >40 years of age, similar to the present study [28].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In our study, the male-to-female ratio was estimated to be 2:1 and 1.4:1 in EGFR-vIII positive cases aged ≤40 years and >40 years, respectively, while in the study of Jose et al, it was found to be 1:1 in ≤40 years and male predominance in >40 years of age, similar to the present study [28].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, a total of six cases were found to be positive for the EGFRvIII mutation (17.1%), which is similar to the findings of another study that investigated 75 GBM cases and found eight cases positive for the EGFRvIII mutation (10.7%) [28]. All of these cases were aged over 40 years.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations